(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
This research takes up hegel’s conception of consciousness and how it may be achieved. In addition to the possibility of this consciousness to be rspresented in both individual and historical contents so that it finds its justification in history more than inside the logical theory of Hegel it self. After that, this research moved to discuss the human self after having achieved its consciousness crossing to afrom ofinner liberation reflected in its historical dynamism based on individval awareness. Since it is impossible for this self to attain its freedom away from being conscious its essence together with its hystorical dynamism, Art’s one of the main aspects of this dynamism knowing that consciousness in evitably produces a sum of relation between history and human self. The same reseach finally discussed the position of Hegel’s Art theory between knowledge and history, and demon strated that the objective of art is to detect the position of history in arts activity because art and history are inseparable that art’s types is the history but the content of art is the historical identity.